Intellectual humility without limits: Magnanimous humility, disagreement and the epistemology of resistance - YIP, Brandon (Institutional Knowledge at Singapore Management University, 2024)
In this paper, I provide a characterisation of a neglected form of humility: magnanimous humility. Unlike most contemporary analyses of humility, magnanimous humility is not about limitations but instead presupposes that one possesses some entitlement in a context. I suggest that magnanimous intellectual humility (IH) consists in a disposition to appropriately refrain from exercising one's legitimate epistemic entitlements because one is appropriately motivated to pursue some epistemic good. I then shown that Magnanimous IH has an important role to play in contexts of disagreement and oppression. It calls on knowing parties to refrain from pressing their epistemic entitlements to facilitate mutual understanding. And it is a virtue that oppressed persons have good reason to cultivate in order to develop meta-lucidity in themselves and others.